The Influence of Nutritional Status on Menarche Age in 6th Grade Elementary School Student - Katrin Li Utari; Feva Tridiyawati (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
The decrease in the age of menarche to a younger age (early menarche) occurs in children at the age of less than 12 years. Young women who are not prepared to face menarche will experience many fears and worries, one of which is pain experienced during the first menstruation. One of the factors that affect early menarche is nutritional status because it can trigger the formation of hormones that cause secondary sexual development. The purpose of this study was to analyze the relationship between nutritional status reflected in the comparison of body weight and age with the incidence of early menarche. This study is a type of observational study with a case-control type design. The location used for this research is at SDN Suradita (Suradita elementary school) in June 2023. The sample was based on the ideal proportion of cases and controls, which was 1:1 with 20 female students who had early menarche and 20 female students who had not menarche. The bivariate analysis used is the Chi-Square test. The results of the chi-square analysis resulted in an odds ratio value (OR: 4.3; 95% Confident Interval 1.15 – 16.32; p value 0.028) it can be concluded that a child suffering from obesity is more at risk of early menarche up to 4 times than adolescents who have ideal body weight and are statistically significant